Insights into the origin of rare haplogroup C3* Y chromosomes in South America from high-density autosomal SNP genotyping. (March 2015) - Mezzavilla, Massimo; Geppert, Maria; Tyler-Smith, Chris; Roewer, Lutz; Xue, Yali
Highlights: Revisited the previous discovery of a rare Y haplogroup in two Ecuador populations. Hypotheses for the origin of the haplogroup tested with autosomal SNP genotype data. We favoured one of the three hypotheses, 'founder plus drift'. Abstract: The colonization of Americas is thought to have occurred 15–20 thousand years ago (Kya), with little or no subsequent migration into South America until the European expansions beginning 0.5 Kya. Recently, however, haplogroup C3* Y chromosomes were discovered in two nearby Native American populations from Ecuador. Since this haplogroup is otherwise nearly absent from the Americas but is common in East Asia, and an archaeological link between Ecuador and Japan is known from 6 Kya, an additional migration 6 Kya was suggested. Here, we have generated high-density autosomal SNP genotypes from the Ecuadorian populations and compared them with genotypes from East Asia and elsewhere to evaluate three hypotheses: a recent migration from Japan, a single pulse of migration from Japan 6 Kya, and no migration after the First Americans. First, using forward-time simulations and an appropriate demographic model, we investigated our power to detect both ancient and recent gene flow at different levels. Second, we analyzed 207, 321 single nucleotide polymorphisms from 16 Ecuadorian individuals, comparing them with populations from the HGDP panel using descriptive and formal tests for admixture. Our simulations revealed good power to detect recent admixture, and that ≥5% admixture 6 Kya ago could be detected. However, in the experimental data we saw no evidence of gene flow from Japan to Ecuador. In summary, we can exclude recent migration and probably admixture 6 Kya as the source of the C3* Y chromosomes in Ecuador, and thus suggest that they represent a rare founding lineage lost by drift elsewhere.